I need a single recursive function to compute the series S=1! + 2! + 3! + ...+n!
.
我需要一个递归函数来计算级数S=1!+ 2 !+ 3 !+……+ n !。
I've done it using 2 functions.
我用了两个函数。
void main()
{
int terms=4;
printf(sum(terms)); //outputs 33
/*
terms is the number of terms in the series
e.g. terms=3 outputs 9, 4 outputs 33
*/
}
int fac(int n)
{
return n<2 ? 1 : n * fac(n-1) ;
}
int sum(int terms)
{
return terms>0 ? (fac(terms) + sum(terms-1)):0 ;
}
4 个解决方案
#1
0
This is the simplest I could get it:
这是我能得到的最简单的:
int sum_fac(int target, int counter) {
return (target == counter) ? target : counter * (1 + sum_fac(target, counter + 1));
}
Which when called like this:
当这样称呼的时候:
int main() {
for (int i = 1; i < 10; i++) {
printf("%d: %d\n", i, sum_fac(i, 1));
}
}
Outputs this:
输出:
1: 1
2: 3
3: 9
4: 33
5: 153
6: 873
7: 5913
8: 46233
9: 409113
#2
0
You could have Something like this :
你可以有这样的东西:
int sumOfFac(int currentNumber, int lastSum, int lastFac, int maxNumber)
{
int currentFac = currentNmber*lastFac;
int currentSum = lastSum+currentFac;
if(currentNumber < maxNumber)
{
return sumOfFac(currentNumber+1, currentSum, currentFac, maxNumber);
}
return currentSum;
}
Then you call that function the first time with :
然后你第一次调用这个函数
currentNumber = 1
lastSum = 0
lastFac = 1
maxNumber = your n
#3
0
int main() {
sum(1,terms,1,0);
}
int sum (int cur, int terms, int fac, int sumcur) {
return terms == n? sumcur: sum(cur+1, terms, (cur==1)?1:cur*fac, sumcur+cur*fac);
}
#4
0
a_1 = 1!
a_2 = 1!+2!
...
a_n = a_(n-1) + f_(n-1)*n
where f_i = i!
. So basically we need two outputs from the dunction - a
and f
. Let's translate it to the code:
f_i =我!。所以基本上我们需要两个输出- a和f。让我们把它转换成代码:
int series(int n, int *f)
{
int a, f1;
if (n < 2)
{
*f = 1;
return 1;
}
else
{
a = series(n-1, &f1);
*f = f1 * n;
return a + (*f);
}
}
And then
然后
int main(void) {
int dummy;
printf("%d\n", series(1, &dummy));
printf("%d\n", series(2, &dummy));
printf("%d\n", series(3, &dummy));
printf("%d\n", series(4, &dummy));
return 0;
}
prints this:
打印:
1
3
9
33
Update:
To refactor further, we can say that f_n = a_n - a_(n-1)
, so f_(n-1) = a_(n-1) - a_(n-2)
. Then the recursive case will be:
更新:为了进一步重构,我们可以说f_n = a_n - a_(n-1),因此f_(n-1) = a_(n-1) - a_(n-2)。那么递归的情况是:
a_n = a_(n-1) + (a_(n-1) - a_(n-2))*n
This wont require the calculation of f
, but need some extra bse cases and extra recursive call:
这并不需要计算f,但是需要一些额外的bse情况和额外的递归调用:
int series(int n)
{
int a1, a2;
if (n <= 1)
{
return 1;
}
else if (n==2)
{
return 3;
}
else
{
a1 = series(n-1);
a2 = series(n-2);
return a1 + (a1 - a2)*n;
}
}
#1
0
This is the simplest I could get it:
这是我能得到的最简单的:
int sum_fac(int target, int counter) {
return (target == counter) ? target : counter * (1 + sum_fac(target, counter + 1));
}
Which when called like this:
当这样称呼的时候:
int main() {
for (int i = 1; i < 10; i++) {
printf("%d: %d\n", i, sum_fac(i, 1));
}
}
Outputs this:
输出:
1: 1
2: 3
3: 9
4: 33
5: 153
6: 873
7: 5913
8: 46233
9: 409113
#2
0
You could have Something like this :
你可以有这样的东西:
int sumOfFac(int currentNumber, int lastSum, int lastFac, int maxNumber)
{
int currentFac = currentNmber*lastFac;
int currentSum = lastSum+currentFac;
if(currentNumber < maxNumber)
{
return sumOfFac(currentNumber+1, currentSum, currentFac, maxNumber);
}
return currentSum;
}
Then you call that function the first time with :
然后你第一次调用这个函数
currentNumber = 1
lastSum = 0
lastFac = 1
maxNumber = your n
#3
0
int main() {
sum(1,terms,1,0);
}
int sum (int cur, int terms, int fac, int sumcur) {
return terms == n? sumcur: sum(cur+1, terms, (cur==1)?1:cur*fac, sumcur+cur*fac);
}
#4
0
a_1 = 1!
a_2 = 1!+2!
...
a_n = a_(n-1) + f_(n-1)*n
where f_i = i!
. So basically we need two outputs from the dunction - a
and f
. Let's translate it to the code:
f_i =我!。所以基本上我们需要两个输出- a和f。让我们把它转换成代码:
int series(int n, int *f)
{
int a, f1;
if (n < 2)
{
*f = 1;
return 1;
}
else
{
a = series(n-1, &f1);
*f = f1 * n;
return a + (*f);
}
}
And then
然后
int main(void) {
int dummy;
printf("%d\n", series(1, &dummy));
printf("%d\n", series(2, &dummy));
printf("%d\n", series(3, &dummy));
printf("%d\n", series(4, &dummy));
return 0;
}
prints this:
打印:
1
3
9
33
Update:
To refactor further, we can say that f_n = a_n - a_(n-1)
, so f_(n-1) = a_(n-1) - a_(n-2)
. Then the recursive case will be:
更新:为了进一步重构,我们可以说f_n = a_n - a_(n-1),因此f_(n-1) = a_(n-1) - a_(n-2)。那么递归的情况是:
a_n = a_(n-1) + (a_(n-1) - a_(n-2))*n
This wont require the calculation of f
, but need some extra bse cases and extra recursive call:
这并不需要计算f,但是需要一些额外的bse情况和额外的递归调用:
int series(int n)
{
int a1, a2;
if (n <= 1)
{
return 1;
}
else if (n==2)
{
return 3;
}
else
{
a1 = series(n-1);
a2 = series(n-2);
return a1 + (a1 - a2)*n;
}
}